Procedural Injustice: Indigenous Claims, Limitation Periods, and Laches - McNeil, Kent; Enns, Thomas (Osgoode Digital Commons, 2022)
When Indigenous peoples go to court to seek justice for the historical wrongs they have endured, the Crown often tries to prevent their claims from even being heard by pleading statutes of limitations and laches. The application of these barriers raises serious constitution issues that have been taken account of by the Supreme Court only in the context of declarations of constitutional invalidity. Arguments based on the constitutional division of powers and section 35(1) of the Constitution Act, 1982 have not been addressed by the Court. As a result, limitations statutes that vary from province to province have been applied ad hoc by lower courts, with inconsistent and unjust results. In addition to constitutional concerns, there are also convincing policy reasons why limitations statutes and laches should not be available to deny Indigenous claims in most cases. Access to justice has too often been denied to Indigenous peoples in the past through barriers such as sovereign immunity and federal legislation preventing First Nations from hiring lawyers to pursue their claims. Reconciliation is not promoted by time limits on legal action that perpetuate injustice by continuing to deny Indigenous people access to the courts.